SÍNTESE E CARACTERIZAÇÃO DE COMPÓSITOS DE Zn/La/TiO2 e B/La/TiO2 SUPORTADOS EM BORRACHA NATURAL DE LÁTEX DE HEVEA BRASILIENSES - ALINE SOUSA HERRERO (2023)
Emerging pollutants, pollutants are class mostly recalcitrant. AOPs can be added to conventional water treatment and are successful in removing contaminants. They oxidize organic matter in a non-selective way and produce CO2 and H2O, highlighting the photocatalytic processes with heterogeneous catalysts in AOPs. A widely used photocatalyst is the TiO2 semiconductor, this oxide has been modified in order to expand the geometric structure and preserve the active optical phase, anatase, also to modify the radiation absorption interval, one option is the insertion of boron and lanthanum and zinc and lanthanum, elements of low toxicity and atomic radius for interstitial replacement. With stabilized anatase phase semiconductor, the powder presents the problem of being dispersed, making it necessary to be filtered. Thus, the objective is synthetize semiconductors and composites B/La/TiO2/BN, Zn/La/TiO2/BN after calcination from 400°, 650°C e 900°C. The semiconductors were synthesized using the sol-gel method with a percentage (m/m) of 5% boron and 5% lanthanum and calcined at 400°, 650°, 900° C (BLa400, BLa650, BLa900) and 5% zinc and 5% lanthanum and calcined at 400°, 650°C and 900°C. The powders were supported on natural rubber in order to generate composites with a diameter of 9 cm in a proportion of 15% (m/m). The semiconductors were characterized by TG, DTA, SEM, RDS UV-Vis, XRD, the composites were characterized by SEM. Difractometry showed that the powders calcined at 900°C were converted into the rutile phase and were more crystalline. The RDS attested that the presence of zinc was 5% in the sample, but it was not able to quantify boron and lanthanum. The TG analyzes showed that the powders are thermally stable, losing only moisture, the DTAs demonstrated that the semiconductors BLa400, ZnLa400, BLa650, ZnLa650 convert their anatase phases into rutile from 400° C, the semiconductors calcined at 900° C do not showed a thermal event, confirming that the powder was already in the rutile phase. The RDS UV-Vis demonstrated the spectrometric profile of the samples calcined at 900°C. The micrographs showed that the particles of the powders calcined at 650°C were better dispersed, whereas the materials calcined at 900°C. The composite membranes formed two phases, a polymeric and an inorganic phase, the inorganic phase demonstrated that the particles were homogeneously dispersed on the surface as it is where it is decanted in the drying process, all NR composites presented similar topographical aspect. The synthesis methods proved to be effective for the synthesis of semiconductors and composites. The modification of the semiconductors provided stability in its crystalline geometry at a temperature of 650°C and phase conversion to calcined powders at 900°C, aspects observed by the techniques that were analyzed. The synthesis of composites by the Casting method was effective and provided functional materials with the possibility of application in photocatalysis on supported material.